EFEKTIFITAS SKELING-PENGHALUSAN AKAR DENGAN DAN TANPA APLIKASI SUBGINGIVAL POVIDON-IODIN 10% PADA POKET 5-7mm - Irma Ervina; SW Prayitno; Emile L Supit (Journal of Dentistry Indonesia, 2015)
In deep periodontal lesions, scaling and root planning (SRP) failed to complete elimination of periodontal bacteria, so chemical antimicrobial agents are used topically to destroy microorganism. Povidon-iodin 10% is one of antimicrobial agents that can be applied topically and directly in the pocket. The aim of the research were evaluated the efficacy of povidon-iodin 10% as chemical antimicrobial agents locally applied into periodontal pocket. The data are obtained from patients with chronic adult periodontitis, baseline periodontal pocket depth (PPD) are 5-7 mm. The teeth are scaled and root planed after clinical examinations (plaque index, papilla bleeding index and periodontal pocket depth) and test sites or control sites are assigned randomly. Topically application of povidon-iodin 10% at test sites and aquabides at control sites is applied at day 1st and day 7th. The clinical parameters are assessed at day 14th. The results of the research showed that application of povidon-iodin 10% after SRP provide statistically significant more favorable papilla bleeding index reduction than SRP + aquabides after 14 day. The pocket depth reduction at test sites are greater than control cites (baseline PPD=6 and 7 mm). The conclusions of the research showed that application subgingival povidon-iodin 10% as adjuctive to SRP significantly reduce PBI and PPD (6 & 7 mm) than without application povidon-iodin 10%.